A fast-transient LDO based on buffered flipped voltage follower - Hua Chen; Ka Nang Leung (2010 IEEE International Conference of Electron Devices and Solid-State Circuits, 2010)
In this work, the analysis of the flipped voltage follower (FVF) based single-transistor-control (STC) LDO is given. Two evolved versions of FVF, cascaded FVF (CAFVF) and level shifted FVF (LSFVF), are studied. Then, a buffered FVF (BFVF) for LDO application is proposed, combining the virtues of both CAFVF and LSFVF structures. It alleviates the minimum loading requirement of FVF and the simulation result shows that it has faster transient response and better load regulation.